Jiménez Velásquez, Rossalia. (2020). Efecto de herbicidas pre y post emergente en el cultivo de arroz (Oryza sativa L.) sembrado en condiciones de secano. - Jiménez Velásquez, Rossalia (2020)
Weeds are a limiting factor in agricultural crops, they cause direct and indirect effects due to competition of nutrients, water and light. It is very important to have herbicide alternatives that provide effective control and do not confer resistance to weeds. For this reason, the following research aimed to evaluate the efficiency of different pre and post emergent herbicides in the cultivation of rice (Oryza sativa L.) under rainfed conditions. The investigation was carried out in the Mocache canton, Los Ríos province, in the farm "Four Brothers" located in the “Las Palmas” Enclosure with coordinates 1°12′41”south latitude and 79°26′44″longitude western. The study consisted in the identification of a treatment that presents greater weed control, lower toxicity index, better agronomic characteristics, yield and economic benefits. The treatment of Dichloropropionanilide + 2.4 dichlorophenoxyacetic + Cyhalofop butyl ester, presents the highest effectiveness in the control of weeds with an average of 95%, at 40 days after sowing (dds) in the same way, the treatment Dichloropropionanilide + 2.4 dichlorophenoxyacetic + Cyhalofop butyl ester shows greater control at 40 dds with an average of 91.25%. In the toxicity variable, the herbicide treatments were maintained with a low toxicity at 14 days, a moderate toxicity was obtained in all the treatments. In the case of the evaluation at 21 days, the metsul treatment showed severe toxicity. Among the agronomic characteristics that were evaluated, the treatment of Dichloropropionanilide + 2.4 dichlorophenoxyacetic + Cyhalofop butyl ester presents statistically the highest results with an average of 28 tillers, plant height 68.05 cm, 27 panicles / m2, 185 grains / panicle, 7.38% of Sterility and 1000 grains were obtained an average of 45 grams, these results being statistically higher between treatments in the variables evaluated. The results obtained from the economic analysis recommend the treatment of Dichloropropionanilide + 2.4 dichlorophenoxyacetic + Cyhalofop butyl ester obtained a value of $ 319.67 reflecting a cost benefit ratio of 118.33 this indicates that for every dollar invested a profit of 18 ctvs is obtained with a profitability of 118.33 %. Keywords: prowl, butachlor, propanil, 2.4-D, cleaner, toxicity.